Interpretation of Verses on the 'Parable of the Deeds of Disbelievers': Embodied Islamic Knowledge in Ibn 'Ashur's Maqasid-Based Exegesis - Millah, Dhiya Atul; Nisa’, Khoirun; Albshkar, Hajer Abdallah (Al-Karim: International Journal of Quranic and Islamic Studies, 2024)
This article examines the reinterpretation of verses depicting the "Parable of the Deeds of Disbelievers," focusing on the maqasid-based exegesis approach adopted by Ibn 'Ashur. The study emphasizes the importance of understanding the verses of al-tamthil in the Qur'an, which can be analyzed through various approaches, including linguistic methods such as rhetoric (balaghah), syntax (nahwu), and morphology (sharaf), as well as philosophical approaches like semantics and semiotics. However, this research specifically utilizes the maqasid approach to uncover the deeper objectives and meanings of these verses. This approach has been a subject of academic debate and criticism, highlighting the need for more in-depth studies. This research is a literature review that focuses on a textual analysis, drawing primarily on Ibn 'Ashur's Tafsir al-Tahrir wa al-Tanwir as its main source. The findings reveal that the maqasid approach to the verses of al-tamthil depicting the deeds of disbelievers successfully identifies two primary objectives: "li at-tadabbur" (for contemplation) and "li at-tadzakkur" (for reflection). These objectives suggest that the parables in these verses serve as a means to encourage readers to engage in profound reflection and internalize the wisdom contained within them, thereby fostering embodied Islamic knowledge among the readers of Ibn 'Ashur's maqasid-based exegesis. These findings not only enrich the understanding of Qur'anic texts but also offer a significant contribution to the study of embodied Islamic knowledge within maqasid-based exegesis by demonstrating how this approach can relate the text to broader universal objectives within the framework of maqasid al-shariah. Contribution: This study enriches maqasid-based exegesis by uncovering the meaning of al-tamthil verses and their connection to the objectives of sharia and embodied Islamic knowledge.